Development of big data system of LP3 UNNES to support excellent service of LPTK on international reputation. (June 2020) - Sugianto,; Ngabiyanto,; Prabowo, A; Arfriandi, A
Abstract: Semarang State University, Education and Professional Development Institute (LP3) is a public service institution integrated with the Semarang State University Institute (UNNES). As a public service institution, LP3 is bound by regulations related to service satisfaction and service statistics as part of public accountability. In fact, as a public service institution overseeing services in the fields of PPL, PPG, MKU / MKDK, Career and Counselling, as well as Language and Training services, LP3 does not yet have a qualified DSS. An outline of the research method used in detail was explained as follows: Retrieve Data; Development System; Operation. Based on the results and discussion, it can be seen that building a LPS DSS requires quite a long time. The data in LP3 comes from inhomogeneous forms and varied sources. We conclude that the DSS of LP3 UNNES was going well. The website of data.lp3.unnes.ac.id can be utilized by the community as a decision support system.